Bioefficacy of Some Newer Generation Insecticides Against Chilli Thrips, Scirtothrips dorsalis Hood - Mandal, Laltu; Mondal, Palash (International Journal of Bio-resource and Stress Management, 2022)
An experiment was conducted in the pre-kharif season during the months of January–June of the years 2018 and 2019 at farmer’s field at Benuria, Birbhum, in the lateritic zone of West Bengal, India. ‘Tejaswini’, a promising popular variety, was taken for the study. Four-week old plants were transplanted and plot size was 5.0×5.0 m2, in a Randomized Block Design with thirteen treatments, including control with three replications in both the seasons. Three consecutive sprayings were done at 30, 50 and 70 days after planting. The lowest population of thrips was observed in Broflanilid 20% SC @ 25 g a.i. ha-1 and it was statistically superior over Dinotefuran 20% SG @ 30 g a.i. ha-1, Profenofos 50% EC @ 500 g a.i. ha-1 and Azadirachtin 3% @ 15 g a.i..ha-1.While, non-significant differences in insect populations were recorded among Spinosad 45 % SC @ 73 g a.i. ha-1, Fipronil 5% SC @ 50 g a.i. ha-1, Spirotetramat 15.31% OD @ 60 g a.i. ha-1, Tolfenpyrad 15% EC @ 150 g a.i. ha-1, Imidacloprid 17.80 % SL @ 25 g a.i. ha-1, Thiamethoxam 25% WG @ 25 g a.i. ha-1, λ-cyhalothrin 5% EC @ 15 g a.i. ha-1 and Difenthiuron 50% WP @ 300 g a.i. ha-1, respectively. The newer molecule, Broflanilid 20% SC @ 25 g a.i. ha-1 was found most efficacious against the chilli thrips among the treatments, and this molecule can be recommended to effectively manage the chilli thrips.